Influence of the corrosion of saturated saltwater drilling fluid on the tribological behavior of HVOF WC-10Co4Cr coatings. (January 2017) - Cui, Xiao-yu; Wang, Cheng-biao; Kang, Jia-jie; Yue, Wen; Fu, Zhi-qiang; Zhu, Li-na
Abstract: Drilling fluid which used in drilling process in order to lower the freezing point of drilling fluid also cause severe corrosion and related wear damage to drilling equipment. WC-10Co4Cr surface coatings prepared by high-velocity oxygen-fuel (HVOF) spraying technology were widely used to improve the anti-corrosion and wear resistance properties of drilling tools. The microstructure, phase composition, and mechanical properties of the coatings were analyzed by scanning electron microscope(SEM), X-ray diffraction (XRD) device, and nano-indentation tester. The electrochemical properties of the coatings in saturated saltwater drilling fluid were measured using dynamic potential polarization tester and electrochemical impedance spectroscopy tester. The tribological performance of the samples were determined using CSM ball-on-disk tribometer. The results show that the coatings have dense microstructure, low porosity, and excellent mechanical properties. The potentiodynamic polarization curves show that no negative transformation occurred during the test. The equivalent circuit model of the WC-10Co4Cr coatings in saturated saltwater drilling fluid was established. The friction coefficient of the coatings decreased, and the wear volumes of the coatings increased with the corrodibility of the saturated saltwater drilling fluid increasing. The wear mechanism of the coating corroded by saturated salt drilling fluid include spalling, drop pits of the WC particles, and adhesion. Highlights: The electrochemical failure mechanism of the coatings was micro-galvanic corrosion. The surface porosities increased due to the dissolution of CoCr phase. The friction coefficient decreased and the wear volume increased with the corrodibility increasing.